Recent Progress on Carbon‐Based Electrocatalysts for Oxygen Reduction Reaction: Insights on the Type of Synthesis Protocols, Performances and Outlook Mechanisms - Siyabonga Patrick Mbokazi; Thabo Matthews; Makhaokane Paulina Chabalala; Cyril Tlou Selepe; Dr. Kudzai Mugadza; Dr. Sandile Surprise Gwebu; Prof. Lukhanyo Mekuto; Prof. Nobanathi Wendy Maxakato (ChemElectroChem, 2023)
Abstract Due to their low cost, accessibility of resources, and improved stability and durability, carbon‐based nanomaterials have attracted significant attention as cathode materials for oxygen reduction reactions. These materials also exhibit intrinsic physical and electrochemical features. However, their potential for use in fuel cells is constrained by low ORR activity and slow kinetics. Carbon nanomaterials can be functionalized and doped with heteroatoms to change their morphologies and generate a large number of oxygen reduction active sites to lessen the problems. Doping the carbon lattice with heteroatoms like N, S, and P and functionalizing the carbon structure with −OCH3, −F, −COO−, −O− are two of these modifications that can change specific properties of the carbon nanomaterials like expanding interlayer distance, producing a large number of active sites, and enhancing oxygen reduction activity. When compared to pristine carbon‐based nanomaterials, these doped and functionalized carbon nanomaterials, including their composites, exhibit accelerated rate performance, outstanding stability, and higher methanol tolerance. This article summarizes the most recent developments in heteroatom‐doped and functionalized carbon‐based nanomaterials, covering different synthesis approaches, characterization methods, electrochemical performance, and oxygen reduction reaction mechanisms. As cathode materials for fuel cell technologies, the significance of heteroatom co‐doping and transition metal heteroatom co‐doping is also underlined.